Liver transplantation in patients with alcohol-related liver disease: current status and future directions. (May 2020) - Mathurin, Philippe; Lucey, Michael R
Summary: The survival of patients with alcohol-related liver disease who receive a liver transplant has steadily improved to reach 80–85% at 1 year post-transplantation. The standard requirement for liver transplant—abstinence from alcohol for 6 months before transplantation—has been applied widely, but few data support the use of this rule as the sole criterion for selecting candidates for liver transplantation. When determining the suitability of a patient for transplantation, many liver transplant programmes now try to balance the period of abstinence against the risk of death associated with the severity of liver damage. Data accumulated since 2011 suggest that early liver transplantation (ie, transplantation without a specific period of abstinence) in patients with severe alcoholic hepatitis who do not respond to medical therapy is an effective therapeutic strategy. Further studies are needed to help refine the selection of patients with alcohol-related liver disease who have been abstinent for less than 6 months as suitable liver transplant candidates, and to improve the treatment of alcohol use disorder in those patients who have received a liver transplant.